In-Situ atomic force microscopic observation of ion beam bombarded plant cell envelopes - S. Sangyuenyongpipat (2018)
A program in ion beam bioengineering has been established at Chiang Mai University (CMU), Thailand, and ion beam induced transfer of plasmid DNA molecules into bacterial cells (Escherichia coli) has been demonstrated. However, a good understanding of the fundamental physical processes involved is lacking. In parallel work, onion skin cells have been bombarded with Ar+ions at energy 25 keV and fluence1-2 × 1015ions/cm2, revealing the formation of microcrater-like structures on the cell wall that could serve as channels for the transfer of large macromolecules into the cell interior. An in-situ atomic force microscope (AFM) system has been designed and installed in the CMU bio-implantation facility as a tool for the observation of these microcraters during ion beam bombardment. Here we describe some of the features of the in-situ AFM and outline some of the related work. © 2007.